Digital Tools of a Business Organization Innovative Development - Shatilova Olena V.; Shyshuk Nazarii O. (Problemi Ekonomiki, 2020)
The article deals with topical issues of providing the innovative development of a business organization in the context of its digital transformation. The article aims at studying the essence and role of digital tools in the innovative development of a business organization. Having based the research on a comparative analysis of various interpretations of digital transformation in the modern economic literature, the authors identify the main areas of its influence: digital transformation of society, business environment, employees, and business activities. The connection between digital transformation and the innovative development of a business organization has been analyzed. It has been found out that, on the one hand, digital transformation is a prerequisite for innovative development of a business organization; and on the other hand, an innovative business organization can be both the generator and ambassador of digital transformation promotion. It has been determined that the innovative development of a business organization depends on such digital components as digitalization of employees, business processes, and management. The following digital tools of innovative development of a business organization have been described: digital workplace, communication facilities, document flow, and intelligence system. It has been established that the main factors hindering the «digital well-being» in business organizations are the following: the managers’ ignorance, excessive conservatism, excessive bureaucratization, the presence of a «technological gap» and lack of resources. Promising areas for further research in this area are the development of new digital tools that would complement the list of the existing ones, and the improvement of the mechanisms for their implementation.